PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN APLIKASI WATTPAD UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS PUISI - Suryantoro; Azizah, Susi; Himawan, Riswanda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low writing skills of students in writing lessons are due to boring and uninteresting learning experiences. Therefore, innovation is needed to increase students' enthusiasm in writing lessons and improve their skills. One possible innovation is to implement an enjoyable learning model using innovative media. This research aims to enhance narrative writing skills of students in grade VIII-E of SMPN 12 Malang by applying the problem-based learning model with the assistance of a wattpadapplication. The study employs collaborative classroom action research with two learning cycles involving 30 students. Data collection includes observation and tests, and the data are analyzed using descriptive quantitative analysis. The research findings indicate that the implementation of the problem-based learning model with the assistance of a wattpad application successfully enhances students' poetry writing skills in each learning cycle. In the first cycle, there was a 53% increase in the classical in the classical mastery percentage, while in the second cycle, the mastery percentageimproved to 90%. Thus, the implementation of this learning model contributes positively to enhancing students' writing skills.